The specificity of online journalism. Fake news in the messages of selected Polish politicians in 2022 - Wroński, Kamil (Media - Culture - Social Communication, 2024)
This paper focuses on the analysis of fake news identified in the communications of two prominent Polish politicians, Jarosław Kaczyński and Donald Tusk. The aim of the text is to show untrue statements, explain the reasons why they were made in the public forum, and subsequently present how online outlets such as tvp.info and tvn.24.pl responded to such communications. The study takes advantage of critical analysis of media discourse, which demonstrates that Jarosław Kaczyński uses fake news in his statements to create a vision of an alternative reality so as to discredit political opponents and the allegedly hostile states and supra-state organisations, divert attention from current events and thus generate media hype. Donald Tusk selectively exploits problems currently faced by Poles and attempts to instil a vision of the world in the minds of the public, which the ruling party bears responsibility for. In either case, the aim of such contrived messages was to gain and maintain power. The media respond to manipulation and, therefore, contribute to increasing media hype and deeper political polarisation.